(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The use of perfluorocarbon liquid (PFCL) for short-term tamponade can broaden retinal detachment surgery indications and improve outcomes. However, there is no common opinion regarding the effect of PFCL on the functional state of the retina. It is relevant to compare the effect of PFCL and light silicone oil (SO). Purpose was to study the effect of 30 day PFCL tamponade on bioelectrical functional activity and structure of the retina in rabbits’ eyes and to compare the actions of PFCL, SO (specific gravity<1.0 g/sm3) and saline solution in process using electroretinography (ERG), light optical microscopy (LOM) and electron microscopy (EM) at different time points after tamponade (7, 14, and 30 days). Material and Methods. LOM, EM and ERG were performed in 12 rabbits (24 eyes). All animals underwent closed subtotal vitrectomy followed by 30 day tamponade using PFCL in the right eyes and light SO and saline solution in the left eyes. Bioelectrical functional activity and structure of the retina in rabbits’ eyes were studied in dynamics at time points of 7, 14 and 30 days after tamponade. Results and Discussion. Dysfunction of first-order neurons in peripheral and central retina was determined; the former was expressed in a decrease in amplitude of biological response to flash by 23-100%, respectively, while the state of second-order neurons in the inner retina was normalized due to PFCL action. The comparison of effects of 30 day tamponade using PFCL and SO (specific gravity<1.0 g/sm3) revealed that SO induced more apparent reactivity of photoptic and scotoptic response in the retina (1.4-2.25 times). The retinal structures had similar changes after 30 day tamponade with the tamponading agents used. However, the alterations were reactive, not damaging, and reversible.